Blackberry lily: leopard of summer gardens - Mishra, Pragnyashree; Biswal, Monalisha (Indian Horticulture, 2019)
Blackberry lily, a perennial herb, is native to north-easten states and the himalayas. It is similar in appearance to an iris plant with fan shaped leaves. Its root contains several medically active constituents and is therefore used as an analgesic, antibacterial, anti-inflammatory, purgative, tonic etc. Its flowers can be used both as cut and spray flower. Its variety ‘Freckle Face’ is pest and disease resistant. It is affected by bacterial crown rot, anthracnose and leaf spot disease.